Recent Advances in Applications of Bioactive Egg Compounds in Nonfood Sectors - Zhang, Xiaoying; Chelliappan, Brindha; S, Rajeswari; Antonysamy, Michael (Frontiers in Bioengineering and Biotechnology, 2021)
Egg, a highly nutritious food, contains high-quality proteins, vitamins, and minerals. This food has been reported for its potential pharmacological properties, including antibacterial, anti-cancer, anti-inflammatory, angiotensin-converting enzyme (ACE) inhibition, immunomodulatory effects, and use in tissue engineering applications. The significance of eggs and their components in disease prevention and treatment is worth more attention. Eggs have not only been known as a “functional food” to combat diseases and facilitate the promotion of optimal health, but they also have numerous industrial applications. The current review focuses on different perceptions and non-food applications of eggs, including cosmetics. The versatility of eggs from an industrial perspective makes them a potential candidate for further exploration of several novel components.